Mediation Model of Job Satisfaction Determinants - Galih Panjalu Pramono; Dyah Purwaningrum (Enrichment : Journal of Management, 2022)
The interest in employee job satisfaction continues as it affects many outcomes. The general purpose of this study is to examine the mediating model of job involvement variables, and burnout on the effect of job characteristics having an influence on job satisfaction on employees. The population of this study were employees of a timber company in the city of Semarang, with a sample of 140 respondents. This study uses PLS to test the hypothesis. The results showed that the combination of job characteristics and work involvement and burnout as a mediator can affect job satisfaction, and it was concluded that it was concluded that job characteristics had a significant negative effect on burnout, job characteristics had a significant positive effect on job involvement, job characteristics had no effect on job satisfaction, job involvement work has a significant negative effect on burnout, burnout has a significant negative effect on job satisfaction, job involvement has a significant positive effect on job satisfaction, there is an influence of job characteristics on burnout through job involvement, there is an influence of job characteristics on job satisfaction through burnout, job characteristics on job satisfaction through work engagement.